Diabetes and quality of life, Descriptive study on 40 diabetics: type 1 and 2, Carried out at the day hospital for diabetics in Oued Athmenia w de Mila - AMRANE, Lakhdar; LAARIT, Bachir (Journal of Human Sciences, 2022)
The objective of This reschearch is the study of the relationship between the diabetic impairment and the perceived quality of life in diabetics through th use of a generci suvjective scale SF-36 scale ansd a structured interview in the form of survey. It concerns 40 diabetics of both types : 2à insulin dependent ( type 1) and 2à non insulin dependent ( type 2). Our subjects are divised into :14 women and 2- menf varied ages between 25 ans 65 years old (The average age is 40.5) and of various levels socio- economic education.